Efektivitas Penerapan Kebijakan Subsidi Bahan Bakar Minyak - Sampe, Stefanus (JURNAL ADMINISTRASI BISNIS (JAB), 2023)
Fuel oil subsidies are the main alternative for governments in developing countries, especially fuel-exporting countries, to strengthen domestic industrial development. Through this subsidy policy, fuel oil can be accessed by the wider community at a relatively low price and can encourage various businesses. However, the implementation of this subsidy policy leads problems in the distribution of welfare. This study aims to demonstrate the negative effects of the fuel subsidy policy using qualitative methods. The fuel subsidy policy must be reviewed because it is not on target to help the poor, hoarding fuel stocks, scarcity of fuel stocks in the domestic market and unstable fuel prices in the country which ultimately disrupt various business activities.